Diferenciación de los conceptos de masa, volumen y densidad en los alumnos de BUP, mediante estrategias de cambio conceptual y metodológico - Bullejos de la Higuera, J.; Sampedro Villasan, C. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this paper the results of an experimental study about the differentiation of the concept, of mass (or weight), volume and density among Secondary Students, are shown. Instruction using methodological and conceptual change strategies on learning those concepts seems to be a more effective way to reach an accurate level of differentiation for those concepts.